Religious and Cultural Diversity in Inheritance Law: A Discussion on the Impact of Judicial Will Considerations on the National Legal System in Indonesia - Najamudin, Najamudin; Fautanu, Idzam; Najib, Moh.; Kania, Dede; Ridwan, Ahmad Hasan (Hukum Keluarga Islam IAIN LANGSA, 2024)
The obligatory will regulated in Article 209 of the Compilation of Islamic Law is only for adoptive parents and adopted children, there is no obligatory will for heirs of different religions. On the other hand, there is a need for legal provisions that present a solution to provide part of the inheritance to heirs who do not receive inheritance due to religious differences. The purpose of this research is to analyze the important obligatory will in terms of its necessity, as well as a study of the obligatory will in terms of the procedure or implementation of the obligatory will itself in resolving disputes in court with legal considerations that are certain, fair and beneficial. The research method uses a qualitative method with a normative juridical approach. Primary data was obtained from regulations, laws, verdict numbers: 368 K/AG/1995, 51 K/AG/1999, 16 K/AG/2010, 721 K/AG/2015, 218 K/AG/2016 and 331 K/AG/2018. Supreme Court Decision No. 331 K/AG/2018 as well as the Compilation of Islamic Law (KHI) article 209 and regulations governing mandatory wills, secondary, tertiary data obtained from library studies, books, documents, journals and so on that have the same relevance to this research. The analysis process uses a legal logic approach, which analyzes the norms and laws or regulations that apply in depth, radically, systematically, and logically. The results of this study concluded that the dynamics of religious court decisions regarding compulsory bequests for heirs of different religions vary greatly, some are granted and some are rejected, the consideration depends on the sitting of the case that is disputed in the religious court, while the granting of compulsory bequests for heirs of different religions refers to the opinion who allows it as long as it is a will and the different religion in question is not kafir dzimmi. The effect of this decision becomes jurisprudence as part of the source of law for judges at levels below the Supreme Court. The contribution of the religious court's decision on this matter is that it can become a permanent jurisprudence so that it is proposed as a new article in KHI to fill in the missing article regarding mandatory wills for heirs of different religions.